2002
DOI: 10.1053/ajem.2002.32650
|View full text |Cite
|
Sign up to set email alerts
|

Surfing injuries

Abstract: The purpose of this study was to describe the relative frequency, pattern, and mechanism of surfing injuries. Descriptive data of surfing injuries was collected by using a Web site-based interactive multiple choice survey. Data was collected from May 1998 to August 1999. Completed surveys were obtained from 1,348 individuals reporting 1,237 acute injuries and 477 chronic injuries. Lacerations accounted for 42% of all acute injuries, contusions 13%, sprains/strains 12%, and fractures 8%. Thirty-seven percent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
164
7
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(184 citation statements)
references
References 4 publications
12
164
7
1
Order By: Relevance
“…Fractures occurred in 5.4% of the total injuries, which is similar to the 6.0% result found by Nathanson (7) and higher than the one found in research by Steinman (15) , 2.5%. On the other hand, Lowdon et al (17) have reported 9.0% of occurrence in their sample and Taylor et al (3) , similarly, reported 8.9%.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Fractures occurred in 5.4% of the total injuries, which is similar to the 6.0% result found by Nathanson (7) and higher than the one found in research by Steinman (15) , 2.5%. On the other hand, Lowdon et al (17) have reported 9.0% of occurrence in their sample and Taylor et al (3) , similarly, reported 8.9%.…”
Section: Discussionsupporting
confidence: 81%
“…Concerning the kind of injury, the ones found in the present study are those which most frequently appear in other studies described in the literature (5)(6)(7) . However, other injuries are also described in the literature, such as ocular injuries (8)(9)(10) ; auditory injuries (11)(12) ; injuries produced by contact with marine animals or organisms (13)(14) , among others of less incidence.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations